P17 Anticoagulation for liver fibrosis: a pilot study in hepatitis C infected patients. (16th November 2010) - Dhar, A; Anstee, Q; Cobbold, J; Stove, J; Martinelli, A; Taylor-Robinson, S; Thursz, M
Abstract : Introduction: Therapy directed towards the underlying cause of liver disease is not always successful, and anti-fibrotics are urgently required to slow disease progression in these patients. Recent evidence demonstrates a role for the coagulation cascade in promoting liver fibrosis. It is accepted that thrombin can activate hepatic stellate cells via PAR1 cleavage and we have previously shown that the prothrombotic Factor V Leiden mutation is associated with accelerated fibrosis in chronic HCV infection. Further, in animal studies, we have shown that warfarin anticoagulation ameliorates hepatic fibrosis. There is now an urgent need to evaluate the effect of anticoagulation on hepatic fibrosis in human studies. Aim: To evaluate the safety and impact of warfarin anticoagulation on the progression of liver fibrosis using non-invasive tests in HCV patients: a pilot study. Method: HCV patients (n=10, mean age 49.5 years, range 42–62 years, 6=M, 4=F) with moderate fibrosis (Ishak stage 3–4), who had previously failed anti-viral therapy were enrolled. Routine blood tests, liver stiffness measurements and serum markers of fibrosis (ELF testing), were performed at 0, 8 and 16 weeks. A subset of patients (n=5) had hepatic transit times performed at each time point. Patients were given no anticoagulation between 0 and 8 weeks (observation period) and anticoagulated with warfarin to maintain an INR of 2–3 between 8 and 16 weeks (treatment period). Wilcoxon signed ranks test used to compare paired data. Results: Warfarin anticoagulation significantly reduced median liver stiffness values (8 vs 16 weeks: 9.60 vs 6.90 kPa, p=0.012; 0 vs 16 weeks 7.70 vs 6.90 kPa, p=0.043). There was no significant difference in liver stiffness values between the start and end of the observation period. A non significant trend towards prolongation was seen in mean hepatic transit times following anticoagulation (11.0 vs 12.1 s; p=0.23). There were no significant differences between ELF test scores, serum ALT values and APRI scores following anticoagulation. No serious adverse events were reported during the anticoagulation period. One patient had a minor adverse event, requiring temporary cessation of warfarin treatment, and was excluded from the analysis. Conclusion: A short period of warfarin anticoagulation demonstrated a significant improvement in liver stiffness measurements in HCV patients with pre-existing moderate fibrosis, with no major adverse events. These results suggest that warfarin anticoagulation may have a beneficial effect on liver fibrosis in HCV patients. Larger human studies are required to further evaluate its anti-fibrotic potential.